HYDIN loss-of-function inhibits GATA4 expression and enhances atrial septal defect risk. (June 2020) - Cao, Yu; Guo, Junying; Zhang, Jinping; Li, Li; Wang, Hui; Ren, Wenjun; Jiang, Lihong
Abstract: Background: Mutations affecting cardiac structural genes can lead to congenital heart diseases (CHDs). Axonemal Central Pair Apparatus Protein (HYDIN ) is a ciliary protein previously linked to congenital cardiomyopathy. However, the role of HYDIN in the aetiology of CHDs is thus far unknown. Herein, we explore the function of HYDIN in heart development and CHDs. Methods: The function of HYDIN in cardiac differentiation was assessed in vitro using HYDIN siRNAs, HYDIN overexpression, and HYDIN short hairpin RNA (shRNA)-GATA binding protein 4 (GATA4) cDNA rescue constructs in the human embryonic stem cell (hESC) line HES3. To assess Hydin's function in vivo, we generated shRNA-mediated Hydin knockdown transgenic mice. We characterized the functional mechanisms of the most common human HYDIN variant associated with atrial septal defect (ASD) risk (71098693 mutant, c.A2207C) in cardiac-differentiating HES3 cells. Results: HYDIN functions as a positive regulator of human cardiomyocyte differentiation and promotes expression of cardiac contractile genes in hESC cells. This is mediated through GATA4, a critical transcription factor in heart development. Cardiac-specific Hydin knockdown in vivo leads to Gata4 downregulation and enhanced atrial septal defect (ASD) risk in mice. The c.A2207C HYDIN mutation reduces GATA4 expression in hESC cells. Conclusion: HYDIN loss-of-function inhibits GATA4 expression and enhances ASD risk. We also establish the regulation of a key transcription factor in heart development by a ciliary protein. Highlights: HYDIN positively regulates cardiomyocyte differentiation and upregulates contractile genes. This is mediated through GATA4, a critical transcription factor in heart development. Cardiac-specific Hydin knockdown downregulates Gata4 and enhances ASD risk in mice. The most common HYDIN variant associated with ASD risk reduces GATA4 expression.